Effect of Crushing Peanuts on Fatty Acid and Phenolic Bioaccessibility: A Long-Term Study - Isabella Parilli-Moser; Inés Domínguez-López; Camila Arancibia-Riveros; María Marhuenda-Muñoz; Anna Vallverdú-Queralt; Sara Hurtado-Barroso; Rosa M. Lamuela-Raventós (Antioxidants, 2022)
Background: Peanuts are consumed worldwide and have been linked to multiple health benefits. Processing may affect the bioavailability of peanut bioactive compounds. Therefore, we aim to evaluate the effects of crushing peanuts on the bioavailability of fatty acids and phenolic compounds in healthy adults. Methods: 44 participants from the ARISTOTLE study consumed 25 g/day of whole peanuts (WP) or 32 g/day of peanut butter (PB) for 6 months. Fatty acids and phenolic compounds in peanut products and biological samples were assessed by gas chromatography coupled to flame ionization detection and liquid chromatography coupled to high resolution mass spectrometry, respectively. Results: Plasma concentrations of very long chain saturated fatty acids (VLCSFAs) increased significantly after 6 months of WP or PB intake (p < 0.001 in both cases). Participants in the WP group excreted twice as many VLCSFAs in feces as those in the PB group (p = 0.012). The most abundant polyphenols found in WP and PB were p-coumaric and isoferulic acids. Urinary excretion of isoferulic acid increased after the intake of WP and PB (p = 0.032 and p = 0.048, respectively), with no significant difference observed between interventions. Conclusion: The crushing step in peanut butter production seems to enhance the bioavailability of bioactive compounds.